PENGARUH LIKUIDITAS, PROFITABILITAS, EPS, PBV DAN SIZE TERHADAP TINGKAT PENGEMBALIAN SAHAM PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2014 - Widia Cahya Rahmawati, 12.05.52.0192; Suwarti, Titiek (Students Journal of Accounting and Banking, 2016)
This study aimed to examine and analyze the effect of Liquidity, Profitability, EPS, PBV, and Size of banking that listed in Indonesia Stock Exchange. The population in this research was bank companies listed in Indonesia Stock Exchange in 20122014. A sample of 83 companies. The type of data used was secondary data. The analysis used was multiple linear regression analysis. The results showed that the variable Loan to Deposit Ratio (LDR), Return On Asset (ROA), Earning per Share (EPS) is not significant positive effect on the stock return. Price to Book Value (PBV) significant negatively effect on the stock return. Size significant positive effect on the stock return. Keywords: Liquidity, Profitability, EPS, PBV and Size, Stock Return